Root morphological and anatomical responses to increasing phosphorus concentration of wheat plants grown under salinity - Loudari, Aicha; Mayane, Asmae; Naciri, Rachida; Zeroual, Youssef; Colinet, Gilles; Oukarroum, Abdallah (Plant stress (Amsterdam), 2022)
•Salt stress induced modifications in wheat roots at anatomical and morphological levels.•Soluble P-fertilizers increased root performance and efficiency under salinity.•Polyphosphate showed a positive response at lower phosphorus doses.•Orthophosphate revealed significant results within the increase in P-concentration. Understanding the role of nutrients in the alleviation of salt stress effects and the unrevealed significance of root system architecture for plant adaptation is one of the major research areas in the current context of agriculture. Root anatomy is also a valuable parameter to be considered in understanding how the root system counters soil salinity's effect on plant growth. Although Root Phosphorus Acquisition Efficiency (RPAE) under salt stress differs depending on plant species and the severity of salinity in the rhizosphere, optimising phosphorus (P) nutrition seems to bring positive results. This study was planned to investigate the combined effect of salinity and P-availability on root morphology and anatomy as well as nutrient uptake of wheat plants. A pot experiment was performed in open-field conditions using a Moroccan variety of durum wheat. Special emphasis was placed on how orthophosphate and polyphosphate fertilizer forms and phosphorus doses alter the morphology and anatomy of the roots under salt stress. Two soluble fertilizers were used: an orthophosphate (Ortho-A) and a polyphosphate (Poly-B) were applied at four P levels (0, 30, 45 and 60 ppm of P). Our findings showed that salt stress induced, at both anatomical and morphological levels, a series of modifications in the roots of wheat plants. Compared to salt-stressed and unfertilized plants, soluble P-fertilizers significantly increased soil available P, root P- content, RPAE, root length (RL), root surface area (RSA), root volume (RV), root mass density (RMD), root tissue water content (TWC), number of root tips, vascular cylinder diameter and SD/CT ratio. Furthermore, Poly-B showed a positive response in both morphological and anatomical parameters at lower doses while Ortho-A revealed significant results within the increase in P-concentration. The increased root parameters observed under P-treatments could determine the root performance and efficiency to acquire water and P and their transport to the aboveground organs of wheat plants under salinity.